OsFH15, a class I formin, interacts with microfilaments and microtubules to regulate grain size via affecting cell expansion in rice - Sun, Tiantian (Sci Rep, 2017)
Grain size is an important agronomic trait determining rice yield and is mainly restricted by spikelet hull size. However, it remains largely unknown how the spikelet hull size is regulated. In this study, OsFH15, a class I formin protein in Oryza sativa, was found to be able to regulate the size of cells and spikelet hull. OsFH15-Cas9 and OsFH15-RNAi mutants had decreased grain size with reduced cell length, cell width and cell area of inner epidermal cells of the lemma compared with wild-type plants. By contrast, OsFH15-overexpressed plants had increased grain size with larger cells, as well as more abundant microtubules (MTs) and actin filaments (AFs) arrays. OsFH15 was mainly expressed in shoot apical meristem (SAM), spikelets, spikelet hulls and seeds in rice. In vitro biochemical experiments showed that OsFH15 can efficiently nucleate actin polymerization with or without profilin, can cap the barbed end of AFs, and can bind and bundle both AFs and MTs. OsFH15 can also crosslink AFs with MTs, and preferentially bind MTs to AFs. These results demonstrated that OsFH15 played an important role in grain-size control by affecting cell expansion through regulating AFs and MTs.